2021
DOI: 10.1088/1755-1315/832/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Corroded Steel in Lightweight Concrete: A Review

Abstract: There is an immediate need for reinforced concrete (RC) construction to protect natural resources and environmental sustainability due to a gradual decline in natural resources and a problem in many waste disposal sites used. Reducing natural stones as aggregates in concrete using agriculture waste as aggregate to produce lightweight concrete is an effective way to reduce this problem. Lightweight concrete applications for structural design have long been applied because they significantly benefit design and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…As the pressure load increased, the cracks propagated vertically from the bottom of the beam specimen to indicate tensile fracture under flexure [14]. Continuous load to the beam resulted in the start of steel reinforcement yielding, causing beam failure localization to form macro-cracks [45]. In this case, the ratio between the span length and height of the concrete beam is 520/150 or 3.47, so the concrete beam is predicted to be dominated by a shear failure pattern.…”
Section: Reinforced Concrete Failure Patternmentioning
confidence: 99%
“…As the pressure load increased, the cracks propagated vertically from the bottom of the beam specimen to indicate tensile fracture under flexure [14]. Continuous load to the beam resulted in the start of steel reinforcement yielding, causing beam failure localization to form macro-cracks [45]. In this case, the ratio between the span length and height of the concrete beam is 520/150 or 3.47, so the concrete beam is predicted to be dominated by a shear failure pattern.…”
Section: Reinforced Concrete Failure Patternmentioning
confidence: 99%
“…Aggregate in crushed stone is one of the natural materials often used, so it must be limited to preserve nature. One solution is to use oil palm shells [3] as a substitute for some or all of the aggregate [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to determine the characteristics of OPS concrete, especially regarding its effect on the flexural strength of reinforced concrete (RC) [2][3][4][5]. However, research on using OPS as a replacement for coarse aggregate on the flexural strength of corroded concrete is very limited, except for concrete using recycled concrete aggregate (RCA) [6][7][8][9]. These various studies found that the greater the use of OPS, the more it will affect the value of flexural strength, where a percentage of OPS of 10% has the optimum compressive strength value [10].…”
Section: Introductionmentioning
confidence: 99%